Mix Design Beton Berpori Untuk Lantai Ruang Terbuka Hijau Kabupaten Trenggalek - Mohammad Ali Mahfud Efendi; Arie Wardhono; Bambang Sabariman (Fakultas Teknik Universitas Maritim AMNI Semarang, 2026)
Increased development of urban areas often leads to a reduction in rainwater catchment area, increasing surface runoff and potential inundation. One of the construction technologies that can be used to overcome this problem is pervious concrete, which is a type of concrete with an open cavity structure that allows rainwater to seep directly into the soil. This study aims to analyze the composition of the porous concrete mixture that is optimal for pavement applications in green open space (RTH) areas in Trenggalek Regency. The research method used an experimental approach with variations in coarse aggregate sizes of 5–10 mm, 10–20 mm, and 20–30 mm as well as different combinations of aggregate proportions. The parameters analyzed include the compressive strength of the concrete, porosity, and permeability. The results showed that the combination of aggregate sizes of 10–20 mm and 5–10 mm with a composition of 50%:50% produced the most optimal porous concrete performance with a compressive strength of 22.40 MPa at the age of 28 days, a porosity value of 16.25%, and a permeability of 1.16 cm/s. This value meets concrete quality requirements for light pavement applications such as parking areas and pedestrian paths according to national standards. The results of this study show that the variation in aggregate size has a significant effect on the balance between the mechanical properties and the hydraulic properties of porous concrete. With these characteristics, porous concrete has the potential to be used as a pavement material in green open space areas to increase the ability of rainwater infiltration and support sustainable infrastructure development in Trenggalek Regency.